Mitochondrial DNA (mtDNA) markers reveal low genetic variation and the presence of two honey bee races in Uganda's agro-ecological zones. Issue 2 (15th March 2017) - Kasangaki, Patrice; Nyamasyo, Gideon; Ndegwa, Paul; Kajobe, Robert; Angiro, Christopher; Kato, Agapitus; Masembe, Charles
Abstract : As plant pollinators, honey bees ( Apis mellifera) play a very important role in agricultural and non agricultural crop production. In addition, honey bee products are of nutritional, medicinal, cosmetic and economic value to society. With the current changing trends in Uganda's farming systems, it is important to determine the level of genetic variation, and extent of differentiation in the honey bee population. This will be crucial for a successful honey bee management system for improved productivity and conservation of the honey bees in the different agro-ecological zones of Uganda. To achieve this, we investigated the genetic variation in honey bees from ten agro-ecological zones of Uganda by sequencing the intergenic region of the Mitochondrial DNA (mtDNA) COI-COII. We observed high haplotype diversity (Hd > 0.530) within a majority of the agro-ecological zones except the Southern Highland agro-ecological zone (Hd = 0.154). Both the population structure and the phylogenetic analyses revealed the presence of two honey bee races ( A. m. adansonii and A. m. scutellata ) in Uganda. A. m. adansonii is more widespread in the agro-ecological zones in the northern and eastern parts of Uganda while A. m. scutellata is more spread in the southern and western parts of the country. This is the first exhaustive population genetics research on bees in Uganda, and provides results that are useful to the beekeeping industry for effective management of the honey bee population. These results should be considered while planning beekeeping activities in the country.